(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2025)
This study examines the role of Free Economic Zones (FEZs) in the global economy, focusing on their contributions to international trade, investment attraction, and regional economic development. Free Economic Zones serve as strategic instruments for enhancing competitiveness, stimulating innovation, and facilitating the flow of capital and technology across borders. The research employs a combination of comparative analysis, statistical evaluation, and case studies to assess the effectiveness of FEZs in various countries. Findings indicate that well-managed FEZs significantly increase foreign direct investment, promote industrial diversification, and contribute to sustainable economic growth. The study also highlights challenges such as regulatory inconsistencies, infrastructure limitations, and the need for skilled human capital. Recommendations are provided to optimize FEZ policies and maximize their economic impact.